Effects of Mining Activities on Gerbillus nanus in Saudi Arabia: A Biochemical and Histological Study - Almalki, Ahmed M. (Animals (Basel), 2019)
SIMPLE SUMMARY: Mining is the extraction of materials of economic importance from the earth. It is an important source of employment and economic development. However, mining activities can impact on biodiversity, the environment, and human health, mainly through the emission of large quantities of heavy metals. Our objective was to investigate the impacts of gold mining on the Balochistan gerbil, a rodent that inhabits the natural environments of Saudi Arabia. Our results demonstrate the accumulation of heavy metals in the soil, in Arabian boxthorn plants, and in the different tissues of the gerbils. In addition, the gerbils exhibited liver, kidney, and lung injury associated with decreased antioxidants. These data may be of public interest and may call attention to the evaluation of the impacts of gold mining on the environment and nearby communities. ABSTRACT: Mining can impact the environment, biodiversity, and human health through direct and indirect practices. This study investigated the effects of gold mining on Gerbillus nanus, in relation to organ dysfunction and redox imbalance. Soil samples, Lycium shawii, and G. nanus were collected from a site near a mining plant, and a control site. Soil and L. shawii samples from the mining site showed significantly higher cadmium (Cd), copper (Cu), mercury (Hg), arsenic (As), zinc (Zn), lead (Pb), and vanadium (V) levels. Hepatic, renal, and pulmonary Cd, Pb, Hg, Zn, Cu, Fe, As, and V concentrations were significantly higher in G. nanus from the mining site. Markers of liver and kidney function were elevated in serum, and several histological manifestations were observed in the liver, kidney, and lung of G. nanus from the mining site. Malondialdehyde and nitric oxide levels increased, and glutathione and antioxidant enzymes decreased in the liver and kidney of G. nanus. In conclusion, mining practices trigger tissue damage and oxidative stress in G. nanus that live close to the mining site. These findings can represent a scientific basis for evaluating the environmental and health impacts of mining on nearby communities.